AXIAL CRUSHING ENERGY ABSORPTION CAPACITY OF ALUMINUM ALLOY THIN-WALLED MULTI-CORNER TUBES - SUN HongTu; WANG Jian; SHEN GuoZhe; HU Ping (Jixie qiangdu)
The multi-corner tubes with extra concave corners in cross section were presented to improve energy absorption efficiency of aluminum alloy thin-walled tubes in this paper. The axial crushing energy absorption capacity of square and multicorner aluminum alloy thin-walled tubes was compared with the same cross-sectional perimeter and mass. The improved method of folding element was applied to predict the crushing forces of thin-walled tubes under axial impact. The corners on cross section were discussed for the effect on axial crushing energy absorption capacity of the thin-walled tubes. The results show that the increasing performance of energy absorption of aluminum alloy thin-walled tubes is due to the increasing number of corners on cross section. The number and size of corners both have important effect on the crushing force efficiency of multi-corner tubes.The maximum crushing force efficiency of multi-corner tubes is 11. 6% higher than that of square tubes with the same material consumption of thin-walled tubes. The multi-corner tubes with 12 corners show better energy absorption capacity than the tubes with more corners which could lead to the small size of corners or the unstable deformations. The high axial crushing energy absorption capacity of the multi-corner tubes prefers increasing the corner number and corner size of adjacent sides at the same time.